Amyand’s hernia: case report and literature review - Vazquez-Fong, Diego G.; Gonzalez Villegas, Mariana; Santana-Perez, Carlos A. (International Journal of Research in Medical Sciences, 2025)
Amyand's hernia is the eponym for a cecal appendix-whether inflamed or not-incarcerated within the sac of an inguinal hernia. This type of hernia is uncommon, occurring in approximately 0.5-1% of all inguinal hernias, and most cases are found in children.